2004
DOI: 10.1111/j.1440-1789.2004.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological differences of intraneuronal ubiquitin‐positive inclusions in the dentate gyrus and parahippocampal gyrus of motor neuron disease with dementia

Abstract: Semiquantitative morphological analysis of cerebral intraneuronal ubiquitin-positive tau-negative inclusions, a pathologic marker for motor neuron disease with dementia (MND-D), was performed in the dentate gyrus and parahippocampal gyrus of 20 clinicopathologically confirmed patients with MND-D. The forms of the inclusions were tentatively classified into three types: (i) C-type, consisting of relatively large and intensely stained crescent or circular structures; (ii) L-type, showing fine linear structures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
(61 reference statements)
2
11
0
Order By: Relevance
“…The NCI were rounded, spicular, or skein-like [15,17,27], while the GI resembled similar inclusions reported in the tauopathies [28][29][30][31][32] The NII were lenticular, spindle-shaped, or circular [16,17] and the DN often long and contorted in shape [17,33]. Neurons had a larger shape, nonspherical outline and contained at least some cytoplasm [34], while glial cells comprised small spherical or asymmetrical nuclei without cytoplasm.…”
Section: Morphometric Methodsmentioning
confidence: 83%
“…The NCI were rounded, spicular, or skein-like [15,17,27], while the GI resembled similar inclusions reported in the tauopathies [28][29][30][31][32] The NII were lenticular, spindle-shaped, or circular [16,17] and the DN often long and contorted in shape [17,33]. Neurons had a larger shape, nonspherical outline and contained at least some cytoplasm [34], while glial cells comprised small spherical or asymmetrical nuclei without cytoplasm.…”
Section: Morphometric Methodsmentioning
confidence: 83%
“…NCI also exhibit different morphologies, but the majority are either flame-shaped, e.g., NFT in AD, CBD, and PSP or globose, e.g., PiD, DLB, and NIFID. In contrast, a variety of inclusion morphologies are often present in FTLD-TDP including rounded, spicular, or skein-like inclusions (Davidson et al 2007; Yaguchi et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…HC pathways in PiD may be particularly vulnerable to tau pathology (Garcia-Sierra et al 2000), but occasional a-and b-synuclein-immunoreactive PB have also been observed in the DG in this disorder (Mori et al 2002). A similar distribution of pathology is present in sporadic FTLD-TDP, although to a lesser extent (Yang and Schmitt 2001;Woulfe et al 2001;Rosso et al 2001;Arai et al 2003, Kovari et al 2004Yaguchi et al 2004;Mackenzie et al 2006), including cases with hippocampal sclerosis (HS) (Probst et al 2007), the latter often exhibiting neuronal loss in the subiculum and CA1 (Josephs and Dickson 2007). TDP-43 immunoreactive dendrites have also been observed in HC neurons in the form of RNA granules co-localized with the post-synaptic protein PDS-95 (Wang et al 2008).…”
Section: Discussionmentioning
confidence: 83%